1992
DOI: 10.1182/blood.v79.10.2688.bloodjournal79102688
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of very late activation antigen-3 (VLA-3)/VLA-4 in B-cell non-Hodgkin lymphoma and B-cell chronic lymphocytic leukemia

Abstract: The expression of beta 1 (very late activation antigens, VLA 1–6) and beta 2 integrins (leukocyte adhesion molecules [Leu-CAM]) in cell suspensions from the peripheral blood of 70 patients with B-cell chronic lymphocytic leukemia (B-CLL), 15 patients with leukemic lymphocytic lymphoma of intermediate differentiation (IDL), as well as from the lymph nodes of 20 patients with low/intermediate-grade non- Hodgkin's lymphoma (NHL) was studied with the aim of characterizing their adhesive phenotype and evaluating it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Regarding other b1-integrins, whereas expression of CD49a, CD49b, and CD49f was mainly negative (Baldini et al, 1992) also in our B-CLL series, supervised analysis selected the overexpression of CD49d, usually in association with the above-average expression of CD38, CD29, and CD49e, as a part of the signature identifying one of the two B-CLL subgroups with worse prognosis (group II). This finding is in keeping with a recent report on B-CLL gene expression profiling (Pittner et al, 2003), in which, high levels of CD49d mRNA were found to be part of the signature distinguishing CD38 þ from CD38 -B-CLL cells (Crespo et al, 2003;Gattei et al, 2003;McCarthy et al, 2003;Oppezzo et al, 2003;Degan et al, 2004a;Orchard et al, 2004;Rassenti et al, 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Regarding other b1-integrins, whereas expression of CD49a, CD49b, and CD49f was mainly negative (Baldini et al, 1992) also in our B-CLL series, supervised analysis selected the overexpression of CD49d, usually in association with the above-average expression of CD38, CD29, and CD49e, as a part of the signature identifying one of the two B-CLL subgroups with worse prognosis (group II). This finding is in keeping with a recent report on B-CLL gene expression profiling (Pittner et al, 2003), in which, high levels of CD49d mRNA were found to be part of the signature distinguishing CD38 þ from CD38 -B-CLL cells (Crespo et al, 2003;Gattei et al, 2003;McCarthy et al, 2003;Oppezzo et al, 2003;Degan et al, 2004a;Orchard et al, 2004;Rassenti et al, 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Lacking or low expression of CD11a in B-CLL and NHL (Inghirami et al, 1988;Caligaris-Cappio et al, 1989) was supposed to influence the growth pattern of lymphoma. However, further studies (De Rossi et al, 1993;Baldini et al, 1992;Terpe et al, 1994;Stauder et al, 1989) did not corroborate this hypothesis. Our finding that CD11a (LFA-1) is commonly expressed in B-CLL but not related to clinical course and prognosis is in agreement with the later observations.…”
Section: Discussionmentioning
confidence: 87%
“…Adhesion molecules, such as CD44 and its variant isoforms and integrins, are known to play a pivotal role in cell-cell and cell-stroma interactions involved in proliferation, spread via blood and lymph vessels, tumour invasion and metastasis (Roosien et al, 1989;Hynes, 1992;Gü nthert et al, 1991;Lesley et al, 1993;Ruoslahti & Giancotti, 1989;Stauder & Gü nthert, 1955). Their expression has been widely investigated in lymphoproliferative diseases ( Jalkanen et al, 1991;Baldini et al, 1992;Pals et al, 1989;Terpe et al, 1994;Horst et al, 1990). Whereas CD44 has been shown to correlate with prognosis mainly in diffuse-large cell lymphoma ( Jalkanen et al, 1990( Jalkanen et al, , 1991Pals et al, 1989;Horst et al, 1990;reviewed in Gü nthert et al, 1995), in B-CLL no clear-cut correlation on the prognostic relevance of CD44 expression could be demonstrated (Baldini et al, 1992;Pals et al, 1989;Jalkanen et al, 1990;Erikstein et al, 1993;De Rossi et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mononuclear cell suspensions were obtained from heparinised peripheral blood by means of Ficoll-Hypaque gradient centrifugation. The samples underwent direct immunofluorescence staining with monoclonal antibodies (MoAbs), and the surface immunoglobulins (SIg) were characterised as previously described (12). The MoAbs used were CD45-PerCP, CD10-FITC; CD5-FITC, CD19-PerCP, CD20-PE, CD23-PE, CD11c and CD38-PE (Becton Dickinson, Mountain View, CA, USA); CD43-FITC and CD49d (Immunotech SA, Marseilles, France); CD1c-FITC (Ancell Corporation, Bayport, MN, USA); CD103-FITC (Immuno Quality products, Groningen, The Netherlands); and FMC7-FITC and CD79b-FITC (DAKO, Glostrup, Denmark).…”
Section: Immunophenotype Analysismentioning
confidence: 99%